Cutaneous Presentation of Mesothelioma With a Sarcomatoid Transformation. (May 2018) - Klebanov, Nikolai; Reddy, Bobby Y.; Husain, Sameera; Silvers, David N.; Grossman, Marc E.; Tsao, Hensin
Abstract : Abstract: Malignant pleural mesothelioma is a rare neoplasm of mesodermal origin. Cutaneous involvement of malignant pleural mesothelioma is a very rare entity, with only 11 cases reported in the literature. Here, we describe the case of a 75-year-old man with stage IV epithelioid pleural mesothelioma, presenting with a cutaneous eruption 5 months after initial diagnosis, which revealed sarcomatoid features on skin biopsy. Histological analysis of malignancy progression through immunohistochemical staining of the pleural, lymph node, and skin tissue revealed gradual loss of calretinin and gain of desmin, supporting a transformation from epithelioid to sarcomatoid tissue. To our knowledge, this is the first reported case of an epithelioid to sarcomatoid transformation of malignant pleural mesothelioma manifesting in a cutaneous presentation.